Faktor-Faktor yang Mempengaruhi Persalinan dengan Tindakan Vakum Ekstraksi di RSUD Banyumas - Wulandari, Eka Jatu; Handayani, Rohmi (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2014)
Labor has a good risk to mother or fetus, the risk of illness until death. If the mother or fetus in conditions that lead to complications of labor, then should be done vacuum extraction. Condition that to do a vacuum extraction of the fetus such as umbilical cord prolapse, premature separation of placenta, heart rate pattern that is not kinvicing, and fetal distress. Factors affecting the action of vacuum extraction included age, parity, long stage II and pre-eclampsia.To analyze factors including age, parity, long second stage, the incidence of pre-eclampsia to labor by vacuum extraction in the Banyumas Hospitals in 2011.The study used a survey analitic research with case control approach. The population of study were all birth mothers with vacuum extraction in labor room Banyumas Hospital in 2011 and taken a sample of 324 people consisting of 162 cases samples and 162 control sampels. Methods of data analysis used Chi Square test. Most of mother in labor arenâ€™t at risk age category (64,2%). Most of Â mother in labor parity in the low category (64,8%). Most of mother in labor doesnâ€™t have a long stage II (64,2%). Most of Â mother in labor donâ€™t pre-eclampsia (90,7%). There was an association between age with the action of vacuum extraction on weak category (p = 0,000; Ï= 0,328; OR = 4,665). There was an association between parity with the action of vacuum extraction labor on a weak category (p = 0,000;Â  Ï = 0,431; OR = 9,815). There was an association between long stage II with the action of vacuum extraction on weak category (p = 0,000; Ï = 0,541; OR = 38,500). There was an association between pre-eclampsia with the action of vacuum extraction on weak category (p = 0,002; Ï = 0,168; OR = 3,664). There was an association between age, parity, long stage II, and pre-eclampsia with the incidence of labor by vacuum extraction action. The midwives should provide counseling to pregnant women to prevent the action of vacuum extraction indications during childbirth for example by the ANC on a regular basis. Keywords :Â  Age, parity, long stage II, pre-eclampsia, vacuum extraction